2010
DOI: 10.1002/ange.200906322
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Lithium(I) Salt with a Microporous Structure and Its Gas Sorption Properties

Abstract: Aufnahmefähig: Durch Kombination von Lithium‐Kationen mit Isonicotinat‐ Anionen (1) erhält man ein Salz (siehe Bild; C schwarz, O rot, N blau, Li violett), das H2 , N2 , CO2 und CH4 reversibel aufnehmen und abgeben kann. Der Festkörper liegt als dreidimensionales Gerüst vor, in dessen Mikrokanälen sich Lösungsmittelmoleküle befinden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…One of the two independent L1 linkers generates the 8-membered ring and also contributes to stabilizing the cluster, whereas the other L1 linker is solely bonded to clusters. Polymeric annulated ring systems with alternating 8-and 4-membered rings have previously been observed in Li + MOFs, 10,15,19 and Bu and Feng recently observed alternating 6-and 4membered rings. 55 However, IMP-22 is the first structure containing tricyclic repeat units connected by a polyhedral cluster of Li + cations (Figure 3c).…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…One of the two independent L1 linkers generates the 8-membered ring and also contributes to stabilizing the cluster, whereas the other L1 linker is solely bonded to clusters. Polymeric annulated ring systems with alternating 8-and 4-membered rings have previously been observed in Li + MOFs, 10,15,19 and Bu and Feng recently observed alternating 6-and 4membered rings. 55 However, IMP-22 is the first structure containing tricyclic repeat units connected by a polyhedral cluster of Li + cations (Figure 3c).…”
Section: Resultsmentioning
confidence: 82%
“…Although a small number of coordination polymers with Li + -based nodes had previously appeared in the wider literature, 9 the first Li + -based MOF showing permanent porosity was not reported until 2010 by Abrahams et al using an anionic isonicotinate linker to give a porous MOF which demonstrated modest H2 uptake. 10 Since then, Li + -based MOFs have been reported using linkers as varied as amino acids, thiophenedicarboxylates, and anthraquinones. [11][12][13][14][15][16] These Li + -based MOFs have been shown to display properties such as luminescence, [17][18][19] gas uptake, [20][21] and even have potential applications as electrodes in Li batteries.…”
Section: Introductionmentioning
confidence: 99%
“…[78] Nevertheless, to date, the framework based on only 4-connected lithium nodes remains unknown, even though Li-containing boron imidazolate frameworks and frameworks containing Li-O clusters or chains are known. [9] …”
mentioning
confidence: 99%